Strategi Pembelajaran Kooperatif Tipe STAD Sebagai Solusi Alternatif Dalam Meningkatkan Motivasi Belajar Siswa - Mubadillah, Rosita; Fibriana Miftahus Sa’adah (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Learning motivation is an essential component in supporting the effectiveness of learning, including in Islamic Religious Education (PAI). The reality on the ground shows that PAI learning still faces various challenges, such as low student interest, the use of less varied methods, and limited active participation in the learning process. This condition demands innovation in learning strategies that can increase student motivation and engagement holistically. The Student Teams Achievement Division (STAD) cooperative learning strategy is one relevant alternative. This strategy emphasizes cooperation in heterogeneous groups, individual responsibility, and the provision of rewards for team learning outcomes. The application of STAD in PAI learning enables the creation of a collaborative, healthy competitive learning atmosphere, and is oriented towards shared achievement. This has a positive impact on increasing student learning motivation, both intrinsically and extrinsically. This strategy also encourages the development of social skills and interpersonal concern, which are in line with the Islamic values taught in PAI materials. Thus, the urgency of implementing STAD in PAI learning lies in its contribution to creating an active, meaningful, and contextual learning process, and supporting the achievement of educational goals more optimally.